Childhood Obesity in America - Laura Dawes (Harvard University Press, 2014)
This book is about the changing environment of opinions, practices, and beliefs about childhood obesity in the twentieth century that surrounded and affected children like theseâ€” and many more like them. For Charley, at the beginning of the century, childhood obesity was a rare condition and one that doctors didnâ€™t worry much about. Rather, a degree of plumpness in children was considered both attractive and beneficial. There was even some evidence that a degree of overweight in childhood protected children from infectious disease. Charley, his parents, and the Chicago Daily Tribune journalist who was interviewing them were proud that Americanborn Charley was fatter than another famous fat boy from Austria. Fifteen- year- old â€œJâ€ in 1924 found herself subject to a different set of understandings, and not just because she was a girl. In the 1920s, doctors in America began to see overweight in childhood as a worrying medical condition. Fat youngsters like â€œJâ€ might be â€œgood natured and amiable,â€ thought one pediatrician, but were liable to suffer from â€œlessened powers of endurance and diminished activityâ€ as a result of the strain the excess weight placed on heart and lungs. The main harms of the condition, were, however, considered to be social. â€œJâ€ herselfâ€” a young teenâ€” considered her fatness unattractive. She was a member of the first generation of children to turn to dieting as a way of losing weight.1